1995
DOI: 10.1084/jem.181.2.811
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial vascular cell adhesion molecule 1 expression is suppressed by melanoma and carcinoma.

Abstract: SummaryVascular cell adhesion molecule 1 (VCAM-1) mediates extravasation of circulating leukocytes into inflamed tissues, and presumably, plays a role in the immigration of cytotoxic effector lymphocytes into tumor metastases. Since metastases are rarely cleared by blood-borne cells from the immune system, we asked whether the tumor may escape host defense by interfering with the mechanism of effector cell extravasation. Here we show that in mice and humans, VCAM-1 expression is repressed on tumor-infiltrating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
87
1
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(96 citation statements)
references
References 16 publications
(13 reference statements)
7
87
1
1
Order By: Relevance
“…The immune mechanisms elicited by ECD-TM vaccination reach hyperplastic lesions and halt their progression, but are incapable of dealing with an established carcinoma whose extracellular matrix (34,35), neovessels (36), positive pressure (37), and release of many suppressive factors (38) secure its resistance to immune attack. These factors may also account for the poor ability of ECD-TM vaccination to inhibit TUBO cell challenges.…”
Section: Discussionmentioning
confidence: 99%
“…The immune mechanisms elicited by ECD-TM vaccination reach hyperplastic lesions and halt their progression, but are incapable of dealing with an established carcinoma whose extracellular matrix (34,35), neovessels (36), positive pressure (37), and release of many suppressive factors (38) secure its resistance to immune attack. These factors may also account for the poor ability of ECD-TM vaccination to inhibit TUBO cell challenges.…”
Section: Discussionmentioning
confidence: 99%
“…These vascular abnormalities can increase the interstitial pressure, cause heterogeneous permeability, and promote irregular blood flow (2). Furthermore, angiogenic factors such as vascular endothelial cell (EC) growth factors (VEGF) and fibroblast growth factors can cause downregulation of intracellular adhesion molecule-1/2 (ICAM-1/2), VCAM-1, and CD34 on EC, a phenomenon defined as EC anergy (3). Hence, the interaction of leukocytes with the endothelial lining of vessels is reduced, and effector T cells, regardless of being induced in vivo by vaccination or adoptively transferred (4,5), may be impaired in their migration into tumor sites and cannot exert the antitumor effects necessary to eradicate the tumor (6,7).…”
mentioning
confidence: 99%
“…The homing of T cells to tumors is similarly mediated by tissue-specific adhesion molecules, although the failure of the immune system to effectively eradicate a growing tumor is testimony in part to the fact that tumor homing is inefficient. Interestingly, vascularized tumors down-regulate certain adhesion molecules, such as VCAM-1, ICAM-1, and ICAM-2, thereby preventing T lymphocytes from adhering to the vessels and subsequently migrating into the tumor [1,2,4]. In contrast, § v g 3 integrin is highly expressed by angiogenic vascular endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…This is true for both constitutive recirculation of naive lymphocytes and homing of tumor-reactive lymphocytes into tumors. However, it has been demonstrated that many melanoma and carcinoma actively down-regulate the expression of cell adhesion molecules, such as vascular cell adhesion molecule (VCAM)-1 [1], ICAM-1, and ICAM-2 [2] on the endothelium adjacent to the tumor. Furthermore, endothelial cells of tumor vasculature may be unresponsive to pro-inflammatory cytokines and fail to up-regulate the expression of cell adhesion molecules [3,4].…”
Section: Introductionmentioning
confidence: 99%